Biogeography of the Lizard Genus Tropidurus Wied-Neuwied, 1825 (Squamata: Tropiduridae): Distribution, Endemism, and Area Relationships in South America - de Carvalho, André Luiz Gomes (Public Library of Science, 2013)
Based on comprehensive distributional records of the 23 species currently assigned to the lizard genus Tropidurus, we investigated patterns of endemism and area relationships in South America. Two biogeographic methods were applied, Parsimony Analysis of Endemicity (PAE) and Brooks Parsimony Analysis (BPA). Two areas of endemism were detected by PAE: the first within the domains of the semiarid Brazilian Caatinga, which includes seven endemic species, and the second in the region of the Serranía de Huanchaca, eastern Bolivia, in which three endemic species are present. The area cladograms recovered a close relationship between the Atlantic Forest and areas of the South American open corridor. The results revealed a close relationship among the provinces Caatinga (Cerrado, Parana Forest (Pantanal+Chaco)). The uplift of the Brazilian Central Plateau in the Late Pliocene-Early Pleistocene (4-2 Myr BP) has been interpreted as a major event responsible for isolation and differentiation of biotas along these areas. However, we emphasize that without the establishment of a temporal framework concerning the diversification history of Tropidurus it is premature to correlate cladogenetic events with specific time periods or putative vicariant scenarios. The limiting factors hampering the understanding of the biogeographic history of this genus include (1) the absence of temporal references in relation to the diversification of distinct clades within Tropidurus; (2) the lack of an appropriate taxonomic resolution of the species complexes currently represented by widely distributed forms; and (3) the need for a comprehensive phylogenetic hypothesis. We suggest that these three important aspects should be prioritized in future investigations.